Overdraft Facility Policy and Firm Performance : An Empirical Analysis in Eastern European Union Industrial Firms - Castillo, Leopoldo Laborda; Guasch, Jose Luis (World Bank, Washington, DC, 2012)
This article evaluates the effect of the overdraft facility (or line of credit) policy by comparing a large sample of overdraft facilitated firms and matched non-overdraft facilitated firms from Eastern Europe at the sector level. The sample firms are compared with respect to rates of different performance indicators including: technical efficiency (a Data Envelopment Analysis approach is applied to estimate the technical efficiency level for individual sectors), production workers trained, expenditures on research and development, and export activity. In order to avoid the selectivity problem, propensity score matching methodologies are adopted. The results suggest that a certain level of overdraft facility provided to firms would be needed to stimulate investment in research and development, which will eventually result in increased growth in productivity.